Behavioral repertoire of Kingsleya attenboroughi Pinheiro and Santana 2016 (Crustacea Brachyura) under laboratory conditions. Issue 3 (3rd May 2020) - Do Nascimento, Carlito A.; Do Nascimento, Whandenson M.; Dos Santos Lima, Lucineide; De Macêdo, Rayury S.; Alves Filho, Francisco M.; Pinheiro, Allysson P.
Abstract : Freshwater crabs present cryptic habits and generally live in burrows, rocks and leaves among the vegetation, in streams or rivers. The behavior of Kingsleya attenboroughi, a recently discovered freshwater crab already at considerable risk of extinction, was investigated under laboratory conditions for 12 hr in a light/dark cycle. Nine K. attenboroughi behavioral acts were described in six distinct categories: emersion, immersion, environment exploration, feeding, stance and self-cleaning. The present results show a significant difference in behavior between the 12 hr light/dark cycle, but not between sexes. This study contributes to understanding the physiological needs, ecological interactions and to the development of conservation strategies.